Al-Musytarak al-Lafẓī; Analisis kata Hisāb dalam Surat al-Nūr - Nurul Aini Pakaya (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
Every word is a place that should contain meaning. The meaning drawn from a word must be in accordance with the contents of the place. Neither more nor less. Likewise, the Qur'an cannot be separated from pronunciation and meaning. One word that has many meanings is called Musytarak Lafdzi. Musytarak lafdzi itself is a family of balaghah science. Musytarak Lafdzi in the Qur'an is very much. Researchers limit the study to Surat An-Nur specifically on reckoning pronunciation. The purpose of this study was to determine the pronunciation of hisab in the letter An-Nur, as well as its parts. This research method is descriptive analysis with the type of library research. And the primary source of this research is the Al-Qur'anul Karim and its translations from several sources as well as scientific journals and books related to the studies discussed. The results of this study show that the Hisab pronunciation in the Qur'an is mentioned 81 times. Especially in An-Nur's letter, the reckoning is repeated 4 times with different forms. That is in Verses 11, 15, 39 and 57.